MINAT SISWA TERHADAP EKSTRAKURIKULER PENCAK SILAT SMP NEGERI 7 MUARO JAMBI - Syaiva Najwa; Sukendro; Fitri Diana (LPPM STAI Muhammadiyah Probolinggo, 2025)
Student interest is a feeling of preference and interest in something or activity without anyone telling. Based on observations made atstate junior high school 7 muaro jambi, this extracurricular has been around for 2 years, but was stopped and was held again for 3 months starting in december 2024, where interest was very low. The aim of this research is to find out how high students’ interest in pencak silat extracirricularactivities is. This research design is descriptive quantitative research using survey method with data collection techniques using questionnaries, sampling using techniques total sampling,addresed to the entire population of 430 responden. The result of this research show that students interest in the extracurricular pencak silat of state junior high school 7 muaro jambi on intrinsic indicators is 68% and on extrinsic indicators 76% and the total result is 72%. The conclusion of this research is that students interest in extracurricular pencak silat in the medium category is 72%.